Mulching: Promising technology for the cold arid region in Ladakh - Kumar, Yogesh; Singh, Lokendra; Ankit; Singh, M C; Tripathi, Arunima (Indian Horticulture, 2023)
A covering layer of any material applied on the soil surface is called mulch and the process of covering the solid surface around the plants with organic or synthetic material to create the congenial condition for plant growth, development, and efficient production is termed as mulching. This article discusses the importance of adopting mulch technology in cold arid regions of Ladakh.